Quantitative Morphometric Measurements of the Oropharynx in Obstructive Sleep Apnea Syndrome Using a Laser Depth Measurement Module - Kuo CFJ (Dove Medical Press, 2020)
Chung-Feng Jeffrey Kuo,1 Chun-Shu Lin,2 Cheng-Hsien Chuang,1 Chung-Shen Lin,3 Feng-Shiang Chiu,3 Shao-Cheng Liu3 1Department of Material Science & Engineering, National Taiwan University of Science and Technology, Taipei, Taiwan, Republic of China; 2Department of Radiation Oncology, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan, Republic of China; 3Department of Otolaryngology-Head and Neck Surgery Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan, Republic of ChinaCorrespondence: Shao-Cheng LiuDepartment of Otolaryngology-Head and Neck Surgery, Tri-Service General Hospital, National Defense Medical Center, No. 325, Sec. 2, Cheng-Gong Road, Neihu District, Taipei, Taiwan 114, Republic of ChinaTel +886-2-8792-7192Fax +886-2-8792-7193Email m871435@ndmctsgh.edu.twIntroduction: Current diagnostic routines in obstructive sleep apnea syndrome (OSAS), including drug-induced sleep endoscopy (DISE), provide qualitative data. Quantitative morphometric measurements of oropharyngeal structures remain challenging. This study aims to introduce a special linear laser projection device that can facilitate computer-assisted digitalized analysis and provide important quantitative information for OSAS prediction.Materials and Methods: We used a single-wavelength green three-linear laser to provide the scaling reference, with one at an angle of 8.5 degrees with the other two which were parallel. The oropharyngeal images were divided into two groups: the non-OSAS and OSAS group, after polysomnography. A minimum of three evaluations were carried out to determine the maximum cross-sectional area of the oropharyngeal inlet (CSAOI) and the retropalatal depth.Results: A total of 132 subjects were enrolled in this study, with 76 subjects in the non-OSAS group and 56 cases in the OSAS group. In the non-OSAS group, the CSAOI was significantly larger in males than in females. There was a trend toward deeper retropalatal region in men than in women (14.25 vs 11.76 mm). Correlation analysis revealed that retropalatal depth is significantly related to body height and the CSAOI. The body weight and BMI of patients with OSAS were significantly higher than those of participants without OSAS. The retropalatal depth and CSAOI were significantly decreased in OSAS patients as compared to those without OSAS. Our new parameter, the oropharyngeal index, showed the most outstanding discrimination by ROC analysis to predict OSAS.Conclusion: Our innovative module can provide reference parameters, which make it possible to directly estimate the objective absolute values of relevant oropharyngeal structures. Our non-invasive approach can be used for outpatient screening, since it allows the identification of potential OSAS patients who should be referred for polysomnography, as many patients do not require DISE early in their evaluation.Keywords: obstructive sleep apnea syndrome, quantitative endoscope, computer-aided diagnostic system, retropalatal depth, cross-sectional area, oropharyngeal inlet